Evaluation of the Knowledge and Awareness Levels of Physicians Working in Family Health Centers in Sivas Province About Child Abuse and Neglect - Bıyıklıoğlu, Orhan; Yücel Beyaztaş , Fatma; Yıldırım, Ali; Bütün, Celal (The Bulletin of Legal Medicine, 2024)
Objective: Child abuse and neglect (CAAN) is a serious public health problem that causes serious injuries and even deaths in exposed children. The aim of this study was to measure the level of knowledge and awareness of physicians working in Family Health Centers in Sivas province center about child abuse and neglect. Methods: In this descriptive and cross-sectional study, the study population consisted of 105 general practitioner family physicians and family medicine specialists working in Sivas city center. A 17-question Descriptive Information Form questioning the sociodemographic characteristics of the participants and the “Scale for the Identification of Symptoms and Risks of Child Abuse and Neglect” were used. Results: Women who participated in our study were found to be more knowledgeable in recognizing the characteristics of children prone to CAAN than men. Physicians aged 40 years and younger were found to be more successful in recognizing child and parent characteristics in CAAN compared to other age groups. Family medicine specialists were more successful in recognizing CAAN than general practitioners. Conclusion: Considering that every individual is the first source of application in the health care system implemented in our country, physicians working in family health centers are health care practitioners who are likely to encounter child abuse and neglect. Therefore, it should be ensured that the awareness and knowledge levels of physicians remain adequate and effective after medical education by increasing and encouraging effective in-house continuing medical education, including current innovations to be made periodically on the subject.